Phosphorus Dynamics in Japanese Blueberry Field: Long-Term Accumulation and Fractionation across Soil Types and Depths - Chun Lu; Soh Sugihara; Haruo Tanaka; Ryosuke Tajima; Shingo Matsumoto; Takuya Ban (Agronomy)
Effective phosphorus (P) management is crucial for optimal blueberry production. However, a comprehensive understanding of phosphorus distribution across soil depths and types after two decades of blueberry cultivation remains a challenge. This study examines pH, EC, SOC (soil organic carbon), Total N (total nitrogen), and phosphorus fractions in soils from Japanese blueberry fields that have been cultivated for over 20 years. The soils selected for this study represent typical soils from long-term blueberry-growing regions in Japan, ensuring the relevance of the findings to these key agricultural areas. Soil samples were gathered from depths of 0–30 cm and 30–60 cm, revealing significant variations in phosphorus content that are influenced by soil properties and fertilization history. Soil types such as KS (Kuroboku soils) and FS (Fluvic soils) show higher Total P accumulation in deeper layers, whereas BFS (Brown Forest soils) and RYS (Red-Yellow soils) accumulate more in shallower layers. Long-term cultivation has led to greater non-labile phosphorus (NLP) accumulation in shallower layers of KS, BFS, and FS soils, indicating strong phosphorus fixation. BFS soil also exhibits increased organic phosphorus (NaOH-Po) at deeper depths. NaOH-Po and NaHCO3-Po, through their interactions with EC and pH, critically modulate the transformation of NLP into labile phosphorus (LP), thereby influencing overall phosphorus and nitrogen dynamics in the soil. These findings underscore the importance of tailored phosphorus fertilization strategies based on blueberry field characteristics, providing a basis for low-input phosphorus fertilization approaches.